2020
DOI: 10.1016/j.adro.2020.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Respiration-Induced Motion in Prone Versus Supine Patient Positioning for Thoracic Radiation Therapy

Abstract: Variations in the breathing characteristics, both on short term (intrafraction) and long term (interfraction) time scales, may adversely affect the radiation therapy process at all stages when treating lung tumors. Prone position has been shown to improve consistency (ie, reduced intrafraction variability) and reproducibility (ie, reduced interfraction variability) of the respiratory pattern with respect to breathing amplitude and period as a result of natural abdominal compression, with no active involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It can be more useful to apply BBD (Belly Board device) for pelvic malignancies whenever the small bowel dose could be a restrictive factor for target dose escalation in clinical routine ( Estabrook et al, 2016 ). For lung cancer, the supine position is superior to prone orientation by mitigating the target margins ( Guy et al, 2020 ). Nevertheless, using spirometry analysis for respiratory gating of lung cancers was also abandoned and replaced by 4D scanners usage to high-risk components management; it avoids the risk of contamination spread from breathing filters and droplet precautions ( Table 4 ) ( Beddok et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be more useful to apply BBD (Belly Board device) for pelvic malignancies whenever the small bowel dose could be a restrictive factor for target dose escalation in clinical routine ( Estabrook et al, 2016 ). For lung cancer, the supine position is superior to prone orientation by mitigating the target margins ( Guy et al, 2020 ). Nevertheless, using spirometry analysis for respiratory gating of lung cancers was also abandoned and replaced by 4D scanners usage to high-risk components management; it avoids the risk of contamination spread from breathing filters and droplet precautions ( Table 4 ) ( Beddok et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the CTV and OARs are close, the PTV margin may be reduced. Moreover, Guy et al reported an increase in respiratory motion based on the body position [31] , and Fontana et al reported that setup motion in the prone position was significantly greater than that in the supine position [32] . Therefore, irradiation with several beams in the supine position is considered a better irradiation method.…”
Section: Discussionmentioning
confidence: 99%
“…XSPT combines the spine image registration algorithm with dynamic compensation of respiratory motion, which can realize spinal radiosurgery in the prone position. Although prone position can overcome the above problems, the stability of the position and the reliability of tracking can be reduced due to the influence of respiration ( 9 , 10 ). Therefore, whether the prone position can be used for spinal tumor treatment needs to be further discussed.…”
Section: Introductionmentioning
confidence: 99%